Expansion Signatures in 35 H II Regions Traced by SOFIA [C II] Emission - T. Faerber; L. D. Anderson; M. Luisi; L. Bonne; N. Schneider; V. Ossenkopf-Okada; A. G. G. M. Tielens; R. Simon; M. Röllig (The Astrophysical Journal)
We analyze the expansion signatures of 35 H II regions mapped in [C II ] 158 μ m emission by the Stratospheric Observatory for Infrared Astronomy. The [C II ] emission primarily traces photodissociation regions (PDRs) at the transition between ionized and neutral gas. The brightness and narrow line width of [C II ] allow us to measure PDR expansion. Bubble-shaped regions often exhibit expansion, while irregular-shaped ones are less likely to. Of the 35 H II regions, 12 (∼34%) exhibit clear expansion in position–velocity diagrams, making them expansion candidates (ECs), with an average expansion velocity of ∼12.2 km s ^−1 . The remaining 23 regions show no clear expansion signatures, though they may still be expanding below detection limits. Blueshifted expansion is more common (eight ECs solely blueshifted, one redshifted, three both), with mean velocities of ∼10.9 km s ^−1 (blueshifted) and ∼13.2 km s ^−1 (redshifted). A comparison of our observations to spherical expansion models supports expansion in eight of 12 ECs. Estimated dynamical ages are 10–100 times shorter than the ionizing star lifetimes, in agreement with the results of previous studies. Of the 35 regions, 14 (∼40%) appear as [C II ] bubbles; nine of the 12 ECs are bubble-shaped. Thermal pressure likely drives expansion in M43, while stellar winds dominate in M17, M42, RCW 120, and RCW 79. For other ECs, available data do not allow a definitive conclusion. Larger samples and more information about ionizing sources are needed to refine our understanding of H II region feedback and evolution.